RNA polymerase I in yeast transcribes dynamic nucleosomal rDNA. - Jones, H; Kawauchi, J; Braglia, P; Alen, C; Kent, N; Proudfoot, N (2007)
RNA polymerase (Pol) I-transcribed ribosomal genes of budding yeast exist as a tandem array (about 150 repeats) with transcription units separated by spacer sequences. Half of these rDNAs are inactivated by repressive chromatin structure, whereas the rest exist in an open conformation transcribed by closely spaced Pol I elongation complexes. Whereas previous studies have suggested that active rDNA is devoid of nucleosomal structure, we demonstrate that active rDNA has nucleosomal structure, according to chromatin immunoprecipitation and biochemical fractionation. Using a yeast strain with reduced numbers of all actively transcribed rDNA repeats, we show that rDNA exists in a dynamic chromatin structure of unphased nucleosomes. Furthermore, it is associated with chromatin-remodeling enzymes Chd1p, Isw1p and Isw2p, whose inactivation causes defects in transcription termination. We suggest that Pol I transcription, like that of Pol II, may be modulated by specific chromatin structures.